The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3855/jidc.9906
|View full text |Cite
|
Sign up to set email alerts
|

Haematological parameters, haemozoin-containing leukocytes in Sudanese children with severe Plasmodium falciparum malaria

Abstract: Introduction: Haemozoin –containing leucocytes (HCL) can be used to predict severe malaria. Methodology: A case –control study was conducted in Singa, Sudan, to investigate the haematological values and HCL in children with severe Plasmodium falciparum malaria. The cases were children with severe P. falciparum malaria (67). The two groups of controls were patients with uncomplicated P. falciparum malaria (63) and healthy children (50). Results: The mean (±SD) age was 5.5 (±3.8) years. In comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 23 publications
5
9
0
Order By: Relevance
“…In the present study, P. falciparum-infected patients showed signi cantly lower median values of Hb, RBC count, MCH, MCHC, neutrophils, lymphocytes and platelets compared to malaria-negative counterparts. In line with the present study, a signi cantly lower median platelet count was found among Sudanese children with falciparum malaria compared to malaria-negative ones [13]. In contrast, a signi cantly higher median WBC count and non-signi cant differences between the median values of Hb and RBC count were observed in infected children [13].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, P. falciparum-infected patients showed signi cantly lower median values of Hb, RBC count, MCH, MCHC, neutrophils, lymphocytes and platelets compared to malaria-negative counterparts. In line with the present study, a signi cantly lower median platelet count was found among Sudanese children with falciparum malaria compared to malaria-negative ones [13]. In contrast, a signi cantly higher median WBC count and non-signi cant differences between the median values of Hb and RBC count were observed in infected children [13].…”
Section: Discussionsupporting
confidence: 90%
“…Hematological abnormalities can contribute to the pathogenesis and complications of the disease [3] and differ according to disease endemicity, nutritional and immune status, co-existence of hemoglobinopathies and demographic factors [6][7][8][9][10][11][12][13][14][15]. Therefore, the pro le of hematological indices can help physicians to predict malaria consequences and to improve malaria case management in different epidemiological situations [12][13][14][15]. Malaria is a leading cause of anemia worldwide and contributes to approximately 25.0% of anemia prevalence in sub-Saharan Africa [16].…”
Section: Introductionmentioning
confidence: 99%
“…Seven studies were conducted in Asian countries, and six studies were conducted in South America. Eight of the articles from five African countries-Ghana [26], Gabon [7,27], Nigeria [28,29], Cameroon [9,30], and Sudan [31]-reported only P. falciparum infection, while seven of the articles in Brazil [15,32,33], Venezuela [34], Republic of Korea [4], Turkey [35], and Ghana [36] reported only P. vivax infection. P. ovale infection was described only in three studies conducted in France [37], Thailand [6], and South Africa [38].…”
Section: General Characteristics Of Included Studiesmentioning
confidence: 99%
“…All articles were published between 1997 and 2019 (Fig 1). Six studies reported 224 cases of severe malaria in their publications [7,27,30,31,36,38]. Most of the severe complications in the studies were severe anemia (21.9%, 49/224), cerebral malaria (13.8%, 31/224), hyperparasitemia (9.8%, 22/224), repeated convulsions (8%, 18/224), more than one complication (3.6%, 8/224), hypotension (3.1%, 7/224), jaundice (2.7%, 6/224), hypoglycemia (1.8%, 4/224), and prostration (0.4%, 1/224).…”
Section: General Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation